Effect of orthopedic insoles on spinal deformity and walking in adolescents with idiopathic scoliosis summary - Li, Yangzheng; Xiaoli, Huang; Ye, Nan; Songjian, Xin; Li, Liu; Qianqi, Huang; Yining, Yan; Li, Changsheng (Frontiers in Pediatrics, 2023)
Objective To observe the effects of scoliosis-specific exercise therapy combined with braces and orthopedic insoles on improved spinal deformity and walking ability in adolescents with idiopathic scoliosis (AIS). Method From September 2019 to September 2020, 60 outpatient AIS patients were distributed into brace group (n = 30) at random and brace combined orthopedic insole group (n = 30). Both groups underwent brace dryness, and the observation group used scoliosis-specific exercise therapy combined with brace therapy, and on this basis, orthopedic insole intervention was added for 8 h per day for 2 months. At the same time, 20 adolescents of the same age with normal spinal development were recruited as a healthy group. GaitScan instruments were used to collect gait and plantar pressure measurements from study subjects. First, the gait and plantar pressure data of AIS patients and healthy groups were compared horizontally to ascertain the abnormal indicators, and then the spinal deformity and the above abnormal indicators were compared between the brace group and the brace combined orthopedic insole group. Outcome The plantar pressure center drift index (CPEI) in the AIS group was higher than that in the healthy group (F = 3.120, P < 0.05), and there were significant differences in the ratio of medial and lateral heel pressure (M/l) and total foot pressure (P < 0.05) between the AIS group and the healthy group, and no noticeable variations were found in the support phase period, walking speed, and proportion of each phase (P > 0.05). After treatment, the Cobb angle was significantly reduced in both the brace group and the brace combined with orthopedic insole group (P < 0.05), and there was no significant difference between the groups (P > 0.05). There were no significant changes in the pressure ratio of CPEI, M/l and bilateral full foot in the brace group (P > 0.05). The CPEI decreased in the brace combined with orthopedic insole group (P < 0.05), and the pressure ratio of M/l and bilateral full foot tended to 1 (P < 0.05), and was better than that in the brace group (P < 0.05). Conclusion Patients with AIS may have local and worldwide asymmetric changes in plantar pressure distribution. The addition of orthopedic insoles has limited effect on improving scoliosis deformity in patients with AIS, but it can effectively improve the abnormal biomechanics of patients with AIS, so that the patient's force tends to be balanced.